Cowpea rotation as a resource management technology for cerealbased systems in the savannas of West Africa - Carsky, J.R.; Vanlauwe, Bernard; Lyasse, O. (2002)
A synthesis of results from the savanna zone of West Africa suggests that cowpea rotation can be considered to be an effective resource management technology in cereal-based systems. Part of the N requirement of cereal crops can be satisfied by cowpea crop rotation. Furthermore, benefits of cowpea rotation are sometimes higher than expected based on the N content of the cowpea crop alone. Reasons for this include substantial root biomass and N, substantial N-sparing by the legume, and other benefits such as reduction in Striga hermonthica, or pests and often diseases, and possibly access to sparingly soluble P. The characteristics to be encouraged to maximize the N benefit are the amount of nitrogen derived from the atmosphere and the amount of N returned in the residues. In addition the data sug gest that (1) the maturity class of the cowpea variety should be as late as possible, (2) the cereal should be planted as soon as possible after cowpea has been harvested, and (3) minimum soil requirements for optimum cowpea growth should be respected. These can be considered as recommendations to be followed if appropri ate for local agroecological and socioeconomic circumstances. A synthesis of results from the savanna zone of West Africa suggests that cowpea rotation can be considered to be an effective resource management technology in cereal-based systems. Part of the N requirement of cereal crops can be satisfied by cowpea crop rotation. Furthermore, benefits of cowpea rotation are sometimes higher than expected based on the N content of the cowpea crop alone. Reasons for this include substantial root biomass and N, substantial N-sparing by the legume, and other benefits such as reduction in Striga hermonthica, or pests and often diseases, and possibly access to sparingly soluble P. The characteristics to be encouraged to maximize the N benefit are the amount of nitrogen derived from the atmosphere and the amount of N returned in the residues. In addition the data sug gest that (1) the maturity class of the cowpea variety should be as late as possible, (2) the cereal should be planted as soon as possible after cowpea has been harvested, and (3) minimum soil requirements for optimum cowpea growth should be respected. These can be considered as recommendations to be followed if appropri ate for local agroecological and socioeconomic circumstances.